Resistance and the Black Freedom Movement - Garrett Graddy-Lovelace; Priscilla McCutcheon; Ashanté Reese; Angela Babb; Jonathan Hall; Eric Sarmiento Eric Sarmiento; Bradley Wilson (Journal of Agriculture, Food Systems, and Community Development, 2020)
First paragraphs: